chứng minh biểu thức (n-1)(3-2n)-n(n+5)chia hết cho 3 với mọi giá trị n

Question

chứng minh biểu thức (n-1)(3-2n)-n(n+5)chia hết cho 3 với mọi giá trị n

in progress 0
Rylee 10 phút 2021-10-05T21:09:03+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-10-05T21:10:18+00:00

    Đáp án:

    Lời giải: (n-1)(3-2n)-n(n+5)= 3n-3-2n^2+2n-n^2-5n

    =-3-3n^2

    =3(-1-n^2)

    => (n-1)(3-2n)-n(n+5) chia hết cho 3 với mọi giá trị của n

    0
    2021-10-05T21:11:01+00:00

    Lời giải:

    Ta có: \((n-1)(3-2n)-n(n+5)\)

    \(=3n-2n^2-3+2n-n^2-5n\)

    \(=-3n^2-3\) chia hết cho \(3\) \(\forall n\)

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )